On ignition of thermonuclear fuels using neutron-nuclei fusion reactions - Murukesapillai, K. (My University, 1991)
Ways to reduce the neutron number density required for the ignition of D-T fuel using exothermic neutron-nuclei fusion reactions have been investigated. It has been found that improvements in particle and energy confinement times by an order of magnitude reduces the minimum neutron number density required for ignition by an order of magnitude. For example, if the particle confinement time τp and the energy confinement time τE are equal and their values are 0.03, 0.3, 3, 30 seconds, the required minimum neutron number densities are 7.0 × 1021, 5.4 × 1020, 6.0 × 1019, and 6.0 × 1014 m-3, respectively. Methods to achieve these densities are also indicated.